Semaglultide targets Spp1+ microglia/macrophage to attenuate neuroinflammation following perioperative stroke - Yan Li; Qiuyue Fan; Rui Pang; Ling Cai; Jie Qi; Weijie Chen; Yueman Zhang; Chen Chen; Weifeng Yu; Peiying Li (Journal of Neuroinflammation)
Abstract Peripheral surgery evokes neuroimmune activation in the central nervous system and modulates immune cell polarization in the ischemic brain. However, the phenotypic change of microglia and myeloid cells within post-surgical ischemic brain tissue remain poorly defined. Using an integrated approach that combines single-cell RNA sequencing with comprehensive biological analysis in a perioperative ischemic stroke (PIS) model, we identified a distinct Spp1-positive macrophage/microglia (Spp1+ Mac/MG) subgroup that exhibit enriched anti-inflammatory pathways with distinct lipid metabolic reprogrammed profile. Moreover, using immunofluorescence staining, we identified the expression of Glucagon-like peptide-1 receptor (GLP1R) in Spp1+F4/80+ cells and Spp1+Iba-1+ cells. Intraperitoneal administration of semaglutide, a GLP1R agonist clinically approved for the treatment of type 2 diabetes mellitus, resulted in a significant reduction of cerebral infarct volume in PIS mice compared to that in ischemic stroke (IS) mice. Meanwhile, semaglutide treatment also increased the proportion of Spp1+Edu+Iba-1+ cells 3 days after PIS. Using high-parameter flow cytometry, immunofluorescence staining and RNA sequencing, we demonstrated that semaglutide treatment significantly attenuated the expression of neuroinflammatory markers in mice following PIS. We also found that semaglutide treatment significantly ameliorated sensorimotor dysfunction up to 3 days after PIS in mice. Our current finding reveal a novel protective Spp1+Mac/MG subset after PIS and demonstrated that it can be upregulated by semaglutide. We propose that targeting Spp1+Mac/MG subsets using semaglutide could serve as a promising strategy to attenuate the exacerbated neuroinflammation in PIS.